2014
DOI: 10.1177/1866802x1400600201
|View full text |Cite
|
Sign up to set email alerts
|

Designing Cabinets: Presidential Politics and Ministerial Instability

Abstract: This article proposes a set of arguments about the strategic use of cabinet appointments by executives in presidential systems. Although recent work has greatly improved our understanding of government formation in presidential countries, most changes to presidential cabinets happen throughout the lifetime of a government and remain poorly understood. I argue that presidents use cabinet changes in response to unexpected shocks and to adjust their governments to changing political and policy circumstances. Weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 47 publications
5
45
0
17
Order By: Relevance
“…Finally, we found that the social and economic variables, GDP per capita, education, and wealth concentration, had surprisingly little explanatory power. 13 The results lend strong support to the importance of political and institutional determinants of policies.…”
Section: Estimation Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…Finally, we found that the social and economic variables, GDP per capita, education, and wealth concentration, had surprisingly little explanatory power. 13 The results lend strong support to the importance of political and institutional determinants of policies.…”
Section: Estimation Resultssupporting
confidence: 68%
“…11 Some of the alleged important differences still hold: All else being equal, (a) government coalitions should occur more frequently in parliamentarism than in presidentialism 12 and; (b) parliamentary governments should be more successful legislatively than presidential ones. 13 However, three key findings contradict earlier views. First, minority governments are not associated with less success for governments to approve the agenda in parliament in both systems.…”
Section: From Regime Types To Separation Of Powers and Rule Of Lawmentioning
confidence: 74%
See 3 more Smart Citations